1 K cryostat with sub-millikelvin stability based on a pulse-tube cryocooler. (January 2016) - DeMann, A.; Mueller, Sara; Field, S.B.
Highlights: A pulse-tube cryocooler is used to liquefy helium from an external gas source. The liquid helium is then pumped to reach a base temperature of 1.1 K. The system exhibits excellent temperature stability of about 25 μK rms. Starting at room temperature, the system reaches base temperature in 3 h. The system uses only a few dollars' worth of helium per day. Abstract: A cryogenic system has been designed and tested that reaches a temperature below 1.1 K, with an rms temperature stability of 25 μ K. In this system a commercial pulse-tube cryocooler is used to liquify helium gas supplied from an external source. This liquid helium enters a 1 K pot through a large-impedance capillary tube, similar to a conventional 1 K system operated from a liquid helium bath. Unlike a conventional system, however, the molar flow rate of the system can be varied by changing the pressure of the incoming helium. This allows for a trade-off between helium usage and cooling power, which has a maximum value of 27 mW. The measured cooling power and fraction of helium exiting the capillary as liquid agree well with predictions based on an isenthalpic model of helium flow through the capillary. The system is simple to use and inexpensive to operate: The system can be cooled to base temperature in about 3 h and, with a flow rate giving a cooling power of 13 mW, the helium cost is around 6 per day.